Идентификация видов Teucrium chamaedrys L. и Teucrium stevenianum Klokov (Lamiaceae L.): хорология, морфология и особенности фенологии в Донбассе - Зубцова, Т.В. (Промышленная ботаника, 2003)
Characteristic of area of species, maps of their distribution in Ukraine and in the south-eastern Ukraine are given. In the course of research the differences in phenological development, in forms of the ovaries in these species and in glandules location on the ovary prominencies have been revealed. It is concluded that Teucrium stevenianum Klokov introduced in the Donetsk Botanical Gardens differs from Teucrium chamaedrys L.